Performance augmentation of solar photovoltaic panel through PCM integrated natural water circulation cooling technique. (July 2021) - Sudhakar, P.; Santosh, R.; Asthalakshmi, B.; Kumaresan, G.; Velraj, R.
Abstract: The performance of the solar photovoltaic (PV) panel is greatly affected by a rise in operating temperature. A combination of phase change material (PCM) and natural water cooling system for effective thermal management of the PV panel is examined to tackle this issue. Experimentation involved incorporating OM 35 PCM at the tedlar surface of the PV panel and water was allowed to flow from the bottom portion of the PCM chamber. Four different cases considering the direction (bottom to top and top to bottom) and period (continuous and maximum allowable temperature mechanism) of cooling water flow were evaluated and compared with the reference panel. Various parameters such as electrical/thermal efficiency, energy balance and exergy analysis of the PV panel with and without cooling are compared and discussed. Experimentation indicated that the performance of the PV panel augmented due to the incorporation of PCM with natural water circulation. Further, it was identified that the top to bottom continuous water supply cooling technique showed better performance than other cases with an increase in average electricity generation, electrical efficiency, power enhancement percentage, average temperature reduction, maximum overall exergy output and exergy efficiency of 11.92%, 12.4%, 13.54%, 5.4 °C, 26.07% and 8.08% respectively. Highlights: OM 35 PCM integrated natural circulation of water was utilised for PV cooling. Continuous and maximum allowable temperature mechanisms were evaluated. Top to bottom continuous water supply technique contributed to effective PV cooling. Increase in electrical and exergy efficiencies were 12.4% and 8.08%.